Achieving safe hands-on defibrillation using electrical safety gloves – A clinical evaluation. (May 2015) - Deakin, Charles D.; Thomsen, Jakob E.; Løfgren, Bo; Petley, Graham W.
Abstract: Introduction: Safe hands-on defibrillation (HOD) will allow uninterrupted chest compression during defibrillation and may improve resuscitation success. We tested the ability of electrical insulating gloves to protect the rescuer during HOD using a 'worst case' electrical scenario. Materials and method: Leakage current flowing from the patient to the 'rescuer' during antero-lateral defibrillation of patients undergoing elective cardioversion was measured. The 'rescuer' maintained firm (20 kgf) contact with the patient during defibrillation, wearing Class 1 electrical insulating gloves while simulating an inadvertent contact with the patient, through an additional wired contact between 'rescuer' and patient. Results: Data from 61 shocks from 43 different patients were recorded. The median leakage current from all defibrillations was 20.0 μA, (range: 2.0–38.5). In total, 18 of the shocks were delivered at 360 J and had a median leakage current of 27.0 μA (range: 14.3–38.5). Conclusion: When using Class 1 electrical insulating gloves for hands-on defibrillation, rescuer leakage current is significantly below the 1 mA safe threshold, allowing safe hands-on defibrillation if the rescuer makes only one other point of contact with the patient.